UPAYA MENINGKATKAN AKTIVITAS SISWA DENGAN PENDEKATAN EXAMPLES NON EXAMPLES PADA PENDIDIKAN DASAR - Wirnita Wirnita; Nirwansyah Nirwansyah (Ensiklopedia Education Review, 2022)
The background of the research is the low value of learning Indonesian in class V SDN 03 Alai Padang. This study aims to increase the activity and discussion of Indonesian language learning students using the Examples Non Examples approach. The measuring instrument in this research activity uses test and non-test instruments. Tests are in the form of quantitative and non-tests are in the form of qualitative. The results of the data analysis obtained by students' activities in discussing increased the average percentage for the first cycle category and for the second cycle category, namely (83.10%) the good category became a better category. good, namely (85.07%). Activity on teachers increased the average percentage from good category from cycle I to cycle II increased from (80.35) very good category to (91.06%). Student learning outcomes in two cycles, namely the first cycle of students who finished studying (85.71%) in very good category and students who had not finished learning (14.28%). While in the second cycle, students who finished studying (96.42%) were in very good category and students who had not finished studying (3.571%), with an average score. So student learning outcomes have reached the indicators of success in the implementation of learning achieved 80%. Based on the results of the study, it can be concluded that there is an increase in learning through student discussion activities and student learning outcomes at the research site in class V SDN 03 Alai Padang with the Examples Non Examples approach.Keywords: Examples Non Examples, Learning Activities, Discussion, Indonesian Language.